Math, asked by gauranshisharma15, 11 months ago

6x + 3y = 6xy , 2x + 4y = 5xy solve with elemination method​

Answers

Answered by mansimisra1
2

Answer:

HEY!! THE ANSWER IS IN THE ATTACHMENT below WITH STEP BY STEP EXPLANATION I HOPE YOU GET IT...AND THIS HELPS YOU:")

HAPPY TO HELP:")

#stayhomestaysafe

Attachments:
Answered by sharmilam19bma025
1

Answer

Step-by-step explanation:

6x + 3y = 6xy -1eqn

2x + 4y = 5xy -2eqn

1 eqn

÷xy

6/y+3/x=6

2 eqn ÷xy

2/y+4/x=5

if p=1/x,q=1/y

6p+3q=6

2p+4q=5

1st eqn multiplied by 2 and 2 nd eqn by 6

by elimination method

12p +6q =12

12p+ 24q= 30

(-)---(-)-------(-)---

0-18q=-18

q=-18/-18

q=1

substitute q=1 in eqn 2

2p+4=6

2p=6-4

p=2/2

p=1

if p= 1/1=1,q=1/1=1

verification

2(1)+4(1)=6

2+4=6

6=6

Similar questions